Catalytic enantioselective synthesis of indanes by a cation-directed 5-endo-trig cyclization - Johnston, C; Kothari, A; Sergeieva, T; Okovytyy, S; Jackson, K; Paton, R; Smith, M (Nature Publishing Group, 2015)
5-Endo-trig cyclizations are generally considered to be kinetically unfavourable, as described by Baldwin's rules. Consequently, observation of this mode of reaction under kinetic control is rare. This is usually ascribed to challenges in achieving appropriate approach trajectories for orbital overlap in the transition state. Here, we describe a highly enantio- and diastereoselective route to complex indanes bearing all-carbon quaternary stereogenic centres via a 5-endo-trig cyclization catalysed by a chiral ammonium salt. Through computation, the preference for the formally disfavoured 5-endo-trig Michael reaction over the formally favoured 5-exo-trig Dieckmann reaction is shown to result from thermodynamic contributions to the innate selectivity of the nucleophilic group, which outweigh the importance of the approach trajectory as embodied by Baldwin's rules. Our experimental and theoretical findings demonstrate that geometric and stereoelectronic constraints may not be decisive in the observed outcome of irreversible ring-closing reactions.